Elastoplastic Characterization of Zn-Cu-Ti Alloy Sheets: Experiments, Modeling, and Simulation - Cruchaga-Ssa., M (Springer, 2022)
In this work, the elastoplastic behavior of Zn20 alloy sheets is characterized via a methodology that encompasses experiments, modeling, and numerical simulations. The experimental campaign includes tensile, compression, shear, and bulge tests. The modeling is based on the Cazacu-Plunket-Barlat 2006 yield criterion and the Swift hardening law, adjusted only from experimental data from the tensile and compression tests. The corresponding material parameters are obtained with a calibration procedure that accounts for the tensile stress-strain curves and Lankford coefficients, along with five directions regarding the sheet s rolling direction. Besides, compression tests were performed to search for evidence of asymmetric behavior. The numerical simulation, carried out with the finite element method (FEM), is used to validate the previous characterization with the shear and bulge tests models. The experimental force-displacement curve and the shear strain contours are the comparison basis for the shear test. For the bulge test, considering different mask geometries (minor to major axis length ratios), plots of the major-minor strain paths and thickness reduction in terms of the dome height are also used to assess the model s predictive capabilities. In general, the obtained numerical results show a good description of the material behavior in the shear and bulge tests. The evolution of the strain field in the bulge test is well represented by the model regardless of the sample orientation and mask configuration. It is finally concluded that the proposed methodology provides a robust model to describe the elastoplastic response of Zn-Cu-Ti (Zn20) alloy sheets subject to different proportional loading conditions. © 2021, ASM International.